Shrinking multiplexed orbital angular momentum to the nanoscale - He, C; Shen, Y; Forbes, A; Booth, MJ (Springer Nature, 2021)
Orbital angular momentum interactions at the nanoscale have remained elusive because the phase structure becomes unresolved. Now researchers have shown how to overcome this with tightly focused beams, demonstrating a record-high six-dimensional encoding in an ultra-dense nanoscale volume.